Development of Numeric Literacy Instruments in Socio-Cultural Context in Banten for Junior High School Students - Hulwani, Almas Zati; Nindiasari, Hepsi; Novaliyosi (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2025)
The results of the Program for International Student Assessment (PISA) show that the literacy of students in Indonesia is low. This shows that Indonesia is still far behind other countries. One of the reasons Indonesian students have low grades is the ineffective learning system in Indonesia. This investigation aims to produce a numeration liaison instrument of the social and cultural context in Banten for high school students. The methods used are research and development or Research and Development. (R&D). Using the Wilson, Oriondo and Antonio models. The results obtained were: 1) a numerational literacy instrument developed that is valid and reliable, 2) has an average difficulty level for each type of question, and 3) a numerational literature instrument developed falls into the category of both in different power tests. So, the tool developed by the researchers deserves to be used as an assessment to measure numerational literacy in the Banten cultural context.